Major impacts on the primary metabolism of the plant pathogen Cryphonectria parasitica by the virulence-attenuating virus CHV1-EP713 - Dawe, Angus L. (Microbiology Society, 2009)
Cryphonectria parasitica, the chestnut blight fungus, can be infected by virulence-attenuating mycoviruses of the family Hypoviridae. Previous studies have led to the hypothesis that the hypovirus-infected phenotype is partly due to metabolic changes induced by the viral infection. To investigate this, we measured the metabolic rate and respiration of C. parasitica colonies grown on solid medium. These experiments supported historical observations of other fungal species done in liquid cultures that the metabolic rate steadily declines with age and differentiation of the mycelium. Hypovirus infection increased metabolic rate in the youngest mycelium, but a subsequent decline was also observed as the mycelium aged. By measuring both CO(2) production and O(2) consumption, we also observed that changes occur in carbohydrate metabolism as a result of ageing in both infected and uninfected mycelium. Mycelium on the periphery of the colony exploited fermentation pathways extensively, before transitioning to aerobic carbohydrate metabolism and finally lipid metabolism in the interior regions, despite abundant remaining glucose. However, the hypovirus affected the extent of these changes, with infected mycelium apparently unable to utilize lipid-related metabolic pathways, leading to an increased depletion of glucose. Finally, we used metabolic profiﬁling to determine the changes in accumulation of primary metabolites in wild-type and hypovirus-infected mycelium and found that approximately one-third of the 164 detected metabolites were affected. These results are consistent with those expected from the physiological measurements, with significant alterations noted for compounds related to lipid and carbohydrate metabolism. Additionally, we observed an increase in the accumulation of the polyamine spermidine in the presence of hypovirus. Polyamines have been implicated in antiviral responses of mammalian systems; therefore this may suggest a novel antiviral response mechanism in fungi.